Corrosion and corrosion control of copper by N-BTA in storage and atmospheric environment by electrochemical technique - Ansari F.A.; Quraishi M.A.; Lal U.S.; Singh A. (My University, 2025)
A simple modified accelerated corrosion test so called Oddy test has been devised to evaluate the corrosivity of showcase construction materials on copper and other artefacts in storage and display. This paper focuses on examining treatment of copper in situ to atmospheric environment by potentiodynamic polarization and electrochemical impedance techniques.The study confirms that nBTA coating on copper acts as mixed type of inhibitor which provides protection in accelerated corrosive environment.